A Contemporary Analysis of Medicolegal Issues in Obstetric Anesthesia Between 2005 and 2015. Issue 1 (March 2020) - Kovacheva, V.P.; Brovman, E.Y.; Greenberg, P.; Song, E.; Palanisamy, A.; Urman, R.D.
Abstract : ( Anesth Analg . 2019;128(6):1199–1207) The study of closed malpractice claims provides the ability to improve medical practice procedures, examine rare complications, and help researchers understand circumstances connected to medical litigation. Professional societies such as The American Society of Anesthesiologists (ASA) and American College of Obstetricians and Gynecologists have used previously closed malpractice claims to enhance patient safety and reduce the likelihood of serious complications. Obstetric anesthesia bears a higher malpractice risk than other anesthesia subspecialties, and numerous safety efforts in the discipline have been implemented to reduce the occurrence of maternal and infant mortality. In this study, the investigators used data from closed claims to identify recent trends in obstetric anesthesia litigation, such as the type of patient injury, associated factors related to the injury, and resulting indemnity payments and litigation costs.